PENERAPAN PASAL 4 UU NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DALAM PEMBERIAN IZIN POLIGAMI DI PENGADILAN AGAMA CIAMIS (STUDI KASUS NOMOR: 3496/PDT.G/2017) - Acep Firman Nurdiansyah; Husni Husni; Tedy Hendrisman (Istinbath | Jurnal Penelitian Hukum Islam, 2019)
The principle of monogamy adhered to by Law Number 1 of 1974 concerning marriage, so efforts to tighten polygamy, namely if desired by the person concerned, because the Law and Religion of the person concerned allows it and has fulfilled several specified conditions. As in article 4 of Law No.1 of 1974 concerning marriage, it states that, among other things, a husband will have more than one wife, so he is obliged to submit an application to the court in the area where he lives, the court which is meant to only give permission to a husband who will have more wife. from a. This article will mainly focus on the views of the Provisions for the Application of Article 4 of the 1974 Law on Marriage in the Granting of Polygamy Permits at the Ciamis Religious Court and to find out the judges' considerations in granting polygamy permits at the Ciamis Religious Court. The methodology of this study is in the form of a qualitative study. The application of this method includes the stages of data collection through observation, interviews, documentation, data analysis and research reports. This study also uses an anthropological approach. This research is a foundation for understanding human behavior according to cultural backgrounds and beliefs humanely. Based on a description of the results of the research and discussion relating to the considerations of the Judge of the Ciamis Religious Court in granting permission for polygamy, the following can be concluded: 1). Application of article 4 of Law Number 1974 case number: 3496 / Pdt.g / 2017 / PA. Ciamis is correct and correct because of the reasons put forward in the case the wife cannot bear offspring. 2). Judges' considerations in the decision number: 3496 / Pdt.g / 2017 / PA. Ciamis has granted permission for polygamy for alternative reasons, namely article 4 paragraph 2 letter c of Law Number 1 of 1974 and the cumulative reasons for article 5 of Law Number 1 of 1974 have been fulfilled.